Local knowledge held by farmers in Eastern Tyrol (Austria) about the use of plants to maintain and improve animal health and welfare. Issue 1 (December 2016) - Vogl, Christian; Vogl-Lukasser, Brigitte; Walkenhorst, Michael
Abstract Background The sustainable management of animal health and welfare is of increasing importance to consumers and a key topic in the organic farming movement. Few systematic studies have been undertaken investigating farmers' local knowledge related to this issue. Ethnoveterinary medicine (EVM) is a discipline focusing on local knowledge and folk methods in veterinary medicine, however most ethnoveterinarian studies primarily address the treatment of animal diseases. Very few studies have explored prophylactic methods. Methods An ethnoveterinary research project in Eastern Tyrol (Austria) was conducted in 2004 and 2005 to gather information about local knowledge of animal husbandry from 144 informants, with the emphasis on plants that maintain livestock health and welfare. Results Informants mentioned a total of 87 plants and 22 plant-based generic terms in the context of maintaining and improving livestock health and welfare. The most important preventive measures for maintaining and improving animal health and welfare were practices related to "fodder" and "feeding". In this category the plants mentioned could be grouped according to three different perceptions about their effect on animals: "Good or bad fodder", "Functional fodder" and "Fodder medicine". In addition to fodder, environmental management, the human-animal relationship, household remedies and cultural/religious activities were also mentioned. When asked about practices in the past that maintained animal health and well-being, interviewees mentioned, for example, the importance of the diversity of sources that used to be available to obtain feed and fodder. Conclusions The informants' approach that feeding is central to livestock welfare is in line with the standard scientific literature on animal health, including in organic farming. Various scientific studies into common fodder evaluate the nutritive and dietary value, efficiency and safety of fodder. Future studies also have to consider the evaluation of traditional, local fodder resources. In fact, the value of 'food as medicine' for humans in the context of local knowledge has been widely assessed, but the potential health benefits of fodder and nutraceuticals in local and traditional ethnoveterinary methods require further attention.